Prospective evidence for physical activity protecting Turkish adults from metabolic disorders - Onat, Altan; Hergenc, Gulay; Kucukdurmaz, Zekeriya; Bulur, Serkan; Kaya, Zekeriya; Can, Gunay (TURKISH SOC CARDIOLOGY, 2007)
Objectives: We inv estigated the role of physical activity levels in predicting incident coronary heart disease (CHD) and certain metabolic disorders and the possible mediation of abdominal obesity. Study design: A total of 3248 participants (1601 men, 1647 women; age 28 years; mean age 48 +/- 12 years) who were enrolled, without a previous diagnosis of CHD, into the Turkish Adult Risk Factor Survey in 1997/98 and 2002/03 were prospectively studied over an eight-year period. Physical activity levels of the participants were categorized as active or sedentary. Metabolic syndrome (MetS) was defined with the ATP-III criteria with modification for male abdominal obesity. Diagnosis of non-fatal CHD was based on history, physical examination, and the Minnesota coding of resting electrocardiograms. The mean follow-up was 6.8 years. Results: The rates of incident hypertension, diabetes, and MetS were 39%, 8.6%, and 25.4%, respectively. After adjustment for gender, age, and waist circumference, the relative risks (RR) calculated for hypertension (RR 0.76; 95% CI 0.63; 0.91), diabetes (RR 0.66; 95% CI 0.49; 0.89), and MetS (RR 0.76; 95% CI 0.60; 0.97) were significantly lower in the physically active group. Protection offered by physical activity was not mainly mediated by waist circumference or C-reactive protein, since protection from abdominal obesity risk did not reach significance. No influence of physical activity was observed on the risks for developing atherogenic dyslipidemia, elevated LDL-cholesterol, and CHD. Exercise significantly protected men from diabetes, and women from hypertension. Overall, protection from metabolic disorders was similar in both sexes. Conclusion: Physical activity, adjusted for gender and age, protects Turkish adults from incident hypertension, diabetes, and MetS. This protection is considered to operate mainly through improvements in blood pressure, beyond the mediation of abdominal obesity and low-grade inflammation.
Keywords: Blood pressure; cohort studies; coronary disease; diabetes mellitus; type 2 exercise; hypertension; metabolic syndrome X/epidemiology; risk factors; Turkey/epidemiology; Cardiovascular System & Cardiology